Cadangan Modul Zikir untuk Amalan Kanak-kanak Autistik Muslim: Planning a Dhikr Module for Muslim Autistic Children Practices - Zainal Abidin, Mohd Syukri; Sa’ari, Che Zarrina; Syed Abdul Rahman, Syed Mohammad Hilmi (Online Journal of Research in Islamic Studies, 2018)
A variety of approaches used by the centers of autism in dealing with autistic children. However, the Academi Fakih Intelek (AFI) in collaboration with the Center of Quranic Research (CQR), University of Malaya has conducted researches on Islamic religious approach to autistic children. AFI is a center of study of the Quran and prayer are trying to open up opportunities for children and adults with autism like to approach the Quran. Although it is not classified as a treatment center, but the greatness of the Quran as a bidder is able to assist the learning of this group. This article proposes a dhikr module that can be practiced by autistic children. This module is formulated based on the collection of data documenting the books of hadith such as the works of scholars and research findings of contemporary researchers. Interviews three teachers in the field of Sufism are to solicit comments and suggestions for improvements. Finally, it can be concluded that dhikr from this module can be applied to autistic children and be able to help address the problems faced by autism.